Deconvolution–convolution treatment on powder diffraction data collected with CuKα X-ray and NiKβ filter. Issue 2 (29th June 2018) - Ida, Takashi; Ono, Shoki; Hattan, Daiki; Yoshida, Takehiro; Takatsu, Yoshinobu; Nomura, Katsuhiro
Abstract : A method to remove small Cu Kβ peaks and step structures caused by Ni K -edge absorption as well as Cu Kα 2 sub-peaks from powder diffraction intensity data measured with Cu-target X-ray source and Ni-foil filter is proposed. The method is based on deconvolution–convolution treatment applying scale transform of abscissa, Fourier transform, and a realistic spectroscopic model for the source X-ray. The validity of the method has been tested by analysis of the powder diffraction data of a standard LaB6 powder (NIST SRM660a) sample, collected with the combination of Cu Kα X-ray source, Ni-foil Kβ filter, flat powder specimen and one-dimensional Si strip detector. The diffraction intensity data treated with the method have certainly shown background intensity profile without Cu Kβ peaks and Ni K -edge step structures.